Evaluation of primer sequence targeting inv A gene of Salmonella sp. by in silico PCR - Abdul Talib, Mohd Afendy; M., Noor Azlina; Radu, Son (American-Eurasian Network for Scientific Information, 2015)
In silico PCR via algorithm and computer simulation aim to provide an easy way to analyse and obtain the theoretical PCR results we may expect from DNA, by using up to date bacterial genomes sequences. In this study, primer set invA-F and invA-R targeting Salmonella invasion gene, invA, was evaluated by in-silico PCR amplification against prokaryotic genome of major foodborne pathogens. A total of 127 strains of bacterial genome sequences from Salmonella sp.(27), Escherichia sp.(59), Listeria sp.(26) and Campylobacter sp.(15) were used as DNA templates in the PCR simulation analysis. The primer set simulatively amplified a single band of 285 bp PCR product with all 25 strains of Salmonella enterica subsp. enterica, whereas no amplification is produced with Salmonella bongori and Salmonella enterica subsp. arizonae. There was no cross-reaction obtained with other bacterial genomes indicated that the primer set is specific to Salmonella enterica subsp. enterica only. PCR experiments using invA-F and invA-R that was carried out in the laboratory had successfully amplified the 285 bp amplicons using DNA from S. Typhimurium, S. Enteritidis, S. Polarum and S. Gallinarum.